Sistem Pakar Diagnosa Penyakit Difteri Dengan Menggunakan Metode Certainty Factor - Sugianto Gea, Waiman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Expert systems are one part of artificial intelligence or AI (Artifical Intelligence) which has recently been experiencing very rapid development. This system is designed to mimic the expertise of an expert into a computer to answer questions and solve problems. An expert is a person who has expertise in a certain field, namely a person who has special knowledge in his / her field. Expert systems are very helpful for decision making, where this expert system can collect and store knowledge from a person or several experts in a knowledge base and use a reasoning system that resembles an expert in solving problems. This expert system uses a certainty factor approach (certainty factors).